(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objectives: Investigate knowledge and practices of female university students in Vietnam regarding menstrual health and menstrual care. Methods: A cross-sectional study through a self-administered questionnaire of 341 students. Results: Students’ knowledge and practices about menstruation are relatively high, passing knowledge rate is 66.3%; practicing reached 78.55%. Conclusion: It is necessary to further strengthen communication and menstruation, and broader, reproductive health education for students, especially focusing on promoting propaganda for both female and male students to help them raise awareness and have the right mindset, practice and offer support about menstrual care.